Environmental Management System: a case study of the operational control implementation on processing of sand in a Foundries Industry - Soares, Antônio Marcos Figueiredo; Fontana, Marcele Elisa; Morais, Danielle Costa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Currently, the industries need to follow some environmental standard. It is due the marketing needs, requisites of the law or by its own ini- tiative. More than satisfying the requirements of any specific standard, the implementation of an environmental management policy, based on standardized procedures, can lead companies to be in accordance with the valid environmental requirements, or to obtain favorable ope- rating results. One of the bases for environmental management is its operational control, because from it all the actions and environmental observations’ values appear for the specific routine administration. Therefore, this paper presents a deployment operational control model of an environmental management in foundry industries. A case study was applied in a foundry industry with sand processing, because the fact of using sand in their production process raises environmental responsibility, due to the specific extraction and manipulation of the product. As a result it was found improvement in the efficiency of the operational activities; this is due, mainly, to tighter control operational, beyond the increase in environmental concern.